2019
DOI: 10.31871/ijntr.5.7.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tarsia Puzzle on Vocabulary Learning in a Primary School Setting

Abstract: Vocabulary learning is essential in learning a particular language as its mastery will greatly affect how learners comprehend the language. Young English as Second Language (ESL) learners with limited vocabulary competence are at risk of being left behind in developing the four language skills. Thus, educators across the world play a key role to ensure pedagogical improvement in teaching vocabulary moves at a rapid pace in academia. As an alternative to a conventional vocabulary lesson, this study applied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Among past local studies reviewed were by Choo (2015), Abdul Rabu and Talib (2017), and Omar and Mohd Said (2019). In Abdul Rabu and Talib's (2017) quasi-experimental study of 70 year four students from a rural primary school, the respondents were classified into two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among past local studies reviewed were by Choo (2015), Abdul Rabu and Talib (2017), and Omar and Mohd Said (2019). In Abdul Rabu and Talib's (2017) quasi-experimental study of 70 year four students from a rural primary school, the respondents were classified into two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moving away from a conventional vocabulary lesson, Omar & Mohd Said (2019) introduced the Puzzle-Based Learning (PBL) for learners' vocabulary acquisition. The aim of the mixed methods research study was to identify the PBL effects on young learners' vocabulary acquisition and their perception of the learning tool in the English as a second language (ESL) context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relevant studies that indicated that the use of games had a significant effect on students' language acquisition used students from the same school or classes with the same teacher (Al-Jarrah, Talafhah & Al-Jarrah, 2019). In other studies, the same group of students acted both as an experimental and as a control group (Omar & Said, 2019;Stavy, Subon & Unin, 2019). Control of the student population and of the teachers involved may be an option for future studies in order to control variables whose presence may have affected the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it made answering reading comprehension questions enjoyable and the whole learning session to be less intimidating for students. Moreover, TARSIA employs the concept of versatility (Omur & Said, 2019), which can be used with all levels of students since the teachers are free to choose any reading texts and generate questions in any way that they perceive as parallel with their students' level.…”
Section: Literature Reviewmentioning
confidence: 99%